Social Work and ICT. - Hill, Andrew, 1952- (SAGE Publications, 2011)
Information and Communication Technologies (ICTs) have become an integral part of social and working lives. Within social work ICTs play a vital role, helping professionals to store and share information and contributing to new forms of practice. This book goes a step further than simply describing ICT skills, but asks why ICT is used and how this affects practice and the experience of people who use services. The book has a practical focus and includes guidance on: Best Practice for Social Work and ICT. ICT Use in Social Work. Service Users, Carers and ICT. Technology and Professional Practic.